Species classification of Tabanus (Diptera: Tabanidae) in Western Thailand: Integrating DNA barcoding and modern morphometrics - Tanasak Changbunjong; Thekhawet Weluwanarak; Sedthapong Laojun; Tanawat Chaiphongpachara (Current Research in Parasitology and Vector-Borne Diseases, 2025)
The species of Tabanus, commonly known as horse flies, are remarkable ectoparasites capable of transmitting various pathogens to animals and humans. Given their role in disease transmission, accurate identification of horse fly species is critical but traditionally relies on morphological characteristics, requiring significant expertise and posing a high potential for error, especially with damaged specimens. To address the limitations of traditional morphological identification, this study highlights the importance of alternative techniques, including DNA barcoding and geometric morphometrics (GM). To enhance the reliability of species identification, DNA barcoding was employed to analyze 30 cytochrome c oxidase subunit 1 (cox1) gene sequences from 15 horse fly species, which were then compared with sequences in the GenBank and BOLD databases. Most cox1 sequences aligned with existing data, with similarity percentages ranging from 96% to 100%. However, discrepancies were noted, including Tabanus helvinus, misidentified as Tabanus aurilineatus, and Tabanus minimus, whose sequences matched those of both Tabanus minimus and Tabanus mesogaeus. Besides DNA barcoding, GM analyses were conducted to enhance species classification accuracy. Our GM analyses employed the landmark-based method for the entire wing and the outline-based method for the first submarginal cell. While shape-based GM analyses demonstrated high reliability, with adjusted total accuracy scores of 97% and 96%, size-based GM analyses yielded significantly lower accuracy, with scores of only 27% and 23%, respectively. These findings provide a foundation for refining horse fly species classification by integrating DNA barcoding and GM approaches, offering valuable advances in species identification and developing targeted control measures.